2007
DOI: 10.1507/endocrj.k06-100
|View full text |Cite
|
Sign up to set email alerts
|

Forty Month Follow-Up of Persistent and Difficultly Controlled Acromegalic Patients Treated with Depot Long Acting Somatostatin Analog Octreotide

Abstract: Abstract. The objective of the present study was to investigate the effects of octreotide long acting release (S-LAR) preparation on GH and IGF-1 serum concentrations and pituitary tumor size in patients with persistent and difficultly controlled acromegaly even after adjuvant irradiation and/or dopamine agonists. Thirty-three patients with active acromegaly (26 female and 7 male, mean age; 43.94 ± 14.01 SD years) were included in this study. Patients were evaluated at baseline and at 6, 12, 30 and 40 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The authors concluded that post-glucose GH levels are not useful for the evaluation of disease control in patients receiving SSAs. Another study found discordant serum IGF-1 and glucose-suppressed GH levels in 41% of patients receiving octreotide LAR [13]. In the current study, discordant IGF-1 and GH levels at week 24 or at early termination were observed in 11 of 49 patients who had both these values available (22.4% of patients).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The authors concluded that post-glucose GH levels are not useful for the evaluation of disease control in patients receiving SSAs. Another study found discordant serum IGF-1 and glucose-suppressed GH levels in 41% of patients receiving octreotide LAR [13]. In the current study, discordant IGF-1 and GH levels at week 24 or at early termination were observed in 11 of 49 patients who had both these values available (22.4% of patients).…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have reported discordant serum IGF-1 and GH levels in patients with acromegaly on SSA therapies [1113]. Discordant values were commonly reported as normal IGF-1 and either high random or post-glucose GH levels, although the reverse has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical results from studies of patients with acromegaly treated with doses of octreotide LAR up to 60 mg/month show a similar safety profile to that reported with conventional treatment (20–30 mg/month) with octreotide LAR. The adverse events reported from patients in the dose-optimization studies discussed above were very similar to conventional therapy with octreotide LAR and report mild adverse events mostly involving the gastrointestinal tract [32, 36, 51, 64]. Some studies reported non-significant increases in gallstones or gallbladder sludge [32, 51, 56].…”
Section: Safety and Tolerability Of Srls Is Maintained At Higher Dosesmentioning
confidence: 95%
“…Few studies have reported results of GH levels measured after an OGTT during medical therapy (12)(13)(14). The utility of an OGTT for monitoring therapeutic responses in these subjects has not been determined.…”
mentioning
confidence: 99%